Self-cleaning sensing type composite coating for fabric and preparation method of self-cleaning sensing type composite coating
Through the combined technology of polypyrrole, iron tetraoxide and hydrophobic polyurea modified coating, the problems of low conductivity and insufficient wave absorption performance of composite fabrics are solved, the conductivity and wave absorption performance are improved, and the service life is extended. It has achieved improvements in self-cleaning and hydrophobic performance.
Patent Information
- Application Number
- CN202411548829.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-07
AI Technical Summary
The existing composite fabrics have low conductivity in the sensing field, difficult to effectively absorb electromagnetic waves, and have a short service life in extreme environments, which is easily affected by pollution.
Using the combined technology of polypyrrole, iron tetraoxide and hydrophobic polyurea modified coating, the composite coating is prepared by in-situ growth and hydrothermal synthesis to build a dense conductive network and superhydrophobic protective layer to enhance the conductivity of the fabric. Wave absorption and self-cleaning performance.
It improves the conductivity and wave absorption properties of composite fabrics, extends service life, enhances the application value in humid environments, and achieves good self-cleaning and hydrophobic properties.
Smart Images

Figure CN119265941A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fabric coatings, and in particular relates to a self-cleaning sensor-type composite coating for fabrics and a preparation method thereof. Background Art
[0002] The inherent comfort and breathability of fabrics make them show great application potential in wearable electronic products such as human thermal management, energy devices, displays and sensors. In the new generation of sensor electronic devices, the use of nanoparticles to modify fabrics and give them multiple properties has received widespread attention, which makes them show great application potential in the fields of human health care, intelligent early warning, etc. For composite fabrics with sensing properties, they are usually impregnated, deposited multiple times and weaved to become conductive elements, and then sewn inside the fabric for human health monitoring and information collection. However, these production methods make the conductive filler and the fabric fiber not tightly combined, resulting in low conductivity of the composite fabric, which limits the use of composite fabrics in the field of sensing.
[0003] With the continuous development of electronic devices, we are surrounded by various electromagnetic radiation waves. The physical damage to vulnerable groups such as infants, pregnant women, etc. has gradually come into people's view, and the demand for anti-electromagnetic radiation fabrics is increasing. In addition, when composite fabrics with sensing properties are worn by the human body, extreme environments such as sweating and rain will also bring huge challenges to the application of composite fabrics. In addition, when the dirt in life comes into contact with the fabric sensor, it not only destroys its beauty, but also limits its service life.
[0004] Therefore, in the field of fabric coating technology, it is of great significance to construct a self-cleaning sensing composite coating with excellent wave absorption and hydrophobic properties while retaining the air permeability and softness of the fabric itself. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a self-cleaning sensor-type composite coating for fabrics. The self-cleaning sensor-type composite coating of the present invention has good self-cleaning performance, sensing performance, wave absorbing performance and hydrophobic performance.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] In a first aspect, the present invention provides a self-cleaning sensor-type composite coating for fabrics, wherein the self-cleaning sensor-type composite coating comprises a polypyrrole coating, a ferrosoferric oxide coating and a hydrophobic polyurea modified coating.
[0008] In a second aspect, a method for preparing the self-cleaning sensor-type composite coating for fabric according to the present invention is provided, the preparation method comprising the following steps:
[0009] Step S1, after activating the fabric in a sodium hydroxide solution, a polypyrrole composite fabric is obtained by in-situ growth of polypyrrole for 1-4 hours, followed by washing and drying to obtain a polypyrrole coating;
[0010] Step S2, placing the dried polypyrrole composite fabric in a dispersion of magnetic ferroferric oxide nanospheres, immersing the fabric in the dispersion, and then drying the fabric to obtain a polypyrrole and ferroferric oxide composite fabric, that is, a ferroferric oxide coating;
[0011] Step S3, adding polydimethylsiloxane and diisocyanate into an organic solvent to react to obtain a polyurea prepolymer, and then adding a fluorine-containing organic substance to obtain a super-hydrophobic polyurea film, that is, a hydrophobic polyurea modified coating;
[0012] Step S4, dissolving the super-hydrophobic polyurea film and the organosiloxane in a mixed solvent and stirring evenly to obtain a mixed dispersion; placing the polypyrrole and ferroferric oxide composite fabric in the mixed dispersion, immersing it in the mixed dispersion, and then drying it to obtain the self-cleaning sensor-type composite coating for the fabric.
[0013] Preferably, the diisocyanate is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, 4,4-diphenylmethane diisocyanate and toluene diisocyanate.
[0014] Preferably, the polydimethylsiloxane is poly(dimethylsiloxane) bis(3-aminopropyl) end-capped; the polydimethylsiloxane needs to be dehydrated at high temperature, and the reaction temperature for generating the polyurea prepolymer is 60-90° C. and the reaction time is 4-8 hours.
[0015] Preferably, the organosiloxane is 1H,1H,2H,2H-perfluorooctyltriethoxysilane.
[0016] Preferably, the magnetic ferroferric oxide nanospheres are prepared by a hydrothermal synthesis method, wherein the temperature of the reaction kettle is 150-240° C. and the time is 8-12 hours.
[0017] Preferably, the immersion treatment time in step S2 is 5-30 min, and the drying temperature in step S2 is 30-60°C; the immersion treatment time in step S4 is 5-30 min, and the drying temperature in step S4 is 30-60°C.
[0018] Preferably,
[0019] The organic solvent in step S3 is selected from one or more of acetone, butanone, ether, toluene, xylene, tetrahydrofuran, ethylene glycol, N,N-dimethylformamide and N,N-dimethylacetamide;
[0020] The fluorine-containing organic compound in step S3 is octafluoro-1,6-hexanediol.
[0021] Preferably, the molar ratio of diisocyanate to fluorine-containing organic matter in step S3 is 1:0-1.
[0022] Preferably, the mixed solvent in step S4 is tetrahydrofuran and anhydrous ethanol, and the volume ratio of the tetrahydrofuran to the anhydrous ethanol is 1 to 3:1.
[0023] Preferably, the mass ratio of the super hydrophobic polyurea film to the organosiloxane in step S4 is 0.5 to 2:1.
[0024] Preferably, the fabric is one of polyester fabric, cotton fabric, silk fabric and wet-spun fabric.
[0025] In a third aspect, a self-cleaning sensing composite coating is provided, wherein the self-cleaning sensing composite coating comprises a polypyrrole coating, a ferrosoferric oxide coating and a hydrophobic polyurea modified coating.
[0026] Preferably, the method for preparing the self-cleaning sensing composite coating comprises the following steps:
[0027] Step S1, after activating the fabric in a sodium hydroxide solution, a polypyrrole composite fabric is obtained by in-situ growth of polypyrrole for 1-4 hours, followed by washing and drying to obtain a polypyrrole coating;
[0028] Step S2, placing the dried polypyrrole composite fabric in a dispersion of magnetic ferroferric oxide nanospheres, immersing the fabric in the dispersion, and then drying the fabric to obtain a polypyrrole and ferroferric oxide composite fabric, that is, a ferroferric oxide coating;
[0029] Step S3, adding polydimethylsiloxane and diisocyanate into an organic solvent to react to obtain a polyurea prepolymer, and then adding a fluorine-containing organic substance to obtain a super-hydrophobic polyurea film, that is, a hydrophobic polyurea modified coating;
[0030] Step S4, dissolving the super-hydrophobic polyurea film and the organosiloxane in a mixed solvent and stirring evenly to obtain a mixed dispersion; placing the polypyrrole and ferroferric oxide composite fabric in the mixed dispersion, immersing it in the mixed dispersion, and then drying it to obtain the self-cleaning sensor-type composite coating for the fabric.
[0031] Preferably, the diisocyanate is selected from one or more of hexamethylene diisocyanate, isophorone diisocyanate, 4,4-diphenylmethane diisocyanate and toluene diisocyanate.
[0032] Preferably, the polydimethylsiloxane is poly(dimethylsiloxane) bis(3-aminopropyl) end-capped; the polydimethylsiloxane needs to be dehydrated at high temperature, and the reaction temperature for generating the polyurea prepolymer is 60-90° C. and the reaction time is 4-8 hours.
[0033] Preferably, the organosiloxane is 1H,1H,2H,2H-perfluorooctyltriethoxysilane.
[0034] Preferably, the magnetic ferroferric oxide nanospheres are prepared by a hydrothermal synthesis method, wherein the temperature of the reaction kettle is 150-240° C. and the time is 8-12 hours.
[0035] Preferably, the immersion treatment time in step S2 is 5-30 min, and the drying temperature in step S2 is 30-60°C; the immersion treatment time in step S4 is 5-30 min, and the drying temperature in step S4 is 30-60°C.
[0036] Preferably,
[0037] The organic solvent in step S3 is selected from one or more of acetone, butanone, ether, toluene, xylene, tetrahydrofuran, ethylene glycol, N,N-dimethylformamide and N,N-dimethylacetamide;
[0038] The fluorine-containing organic compound in step S3 is octafluoro-1,6-hexanediol.
[0039] Preferably, the molar ratio of diisocyanate to fluorine-containing organic matter in step S3 is 1:0-1.
[0040] Preferably, the mixed solvent in step S4 is tetrahydrofuran and anhydrous ethanol, and the volume ratio of the tetrahydrofuran to the anhydrous ethanol is 1 to 3:1.
[0041] Preferably, the mass ratio of the super hydrophobic polyurea film to the organosiloxane in step S4 is 0.5 to 2:1.
[0042] Preferably, the fabric is one of polyester fabric, cotton fabric, silk fabric and wet-spun fabric.
[0043] In a fourth aspect, there is provided application of the self-cleaning sensor-type composite coating for fabrics according to the present invention in the preparation of self-cleaning sensor-type fabrics.
[0044] A fifth aspect provides an application of the self-cleaning sensor type composite coating of the present invention in the preparation of a self-cleaning sensor type fabric.
[0045] Compared with the prior art, the beneficial effects of the present invention are:
[0046] Polypyrrole (PPy) is a conductive polymer containing conjugated double bonds. Through the in-situ growth preparation method, the defect of poor conductivity of textiles (fabrics) can be improved, thus showing great application potential under small deformation and pressure. The good conductivity of fabrics is also conducive to increasing the ability of textiles to absorb electromagnetic waves. The charge transfer process will cause loss of electromagnetic waves, but the result of absorbing electromagnetic waves by charge conduction loss alone is not ideal. Fe3O4 is a strong magnetic nanoparticle. Its application in composite fabrics will greatly increase the wave absorption performance of textiles, thus laying a solid foundation for its application in health care, radiation-proof clothing and other fields. Polyurea is composed of microphase-separated soft and hard segments, with high elastic modulus, anti-flexibility, diverse application shapes and convenient modification. However, unmodified polyurea coatings are hygroscopic underwater or in humid environments. When sweat contacts textiles for a long time, it will destroy the internal conductive network and affect the sensing performance.
[0047] (1) The present invention introduces polypyrrole conductive filler on the fabric surface by in-situ growth and constructs a dense conductive network on the fabric fibers, which gives the composite fabric excellent sensing ability and electromagnetic wave absorption ability, thus overcoming the defect of the existing composite fabric with single performance.
[0048] (2) The present invention deposits the magnetic ferroferric oxide prepared by the hydrothermal synthesis method on the surface of the fabric fiber, so that the composite fabric has a certain magnetic loss capacity, further increasing the composite fabric's ability to absorb electromagnetic waves; and the present invention deposits the magnetic ferroferric oxide prepared by the hydrothermal synthesis method on the surface of the fabric fiber, further enhancing the self-cleaning performance of the composite fabric.
[0049] (3) In order to improve the inherent shortcomings of the coating, such as short service life and performance being easily damaged by an external wet environment, the present invention prepares a modified polyurea and adds an organosiloxane to modify a super-hydrophobic protective coating on the outermost layer of the composite fabric. This not only improves the use limitations of the composite fabric in a wet environment and increases its service life, but also gives it the application value of monitoring human health underwater; in addition, by introducing the super-hydrophobic protective coating of the present invention, the self-cleaning performance, wave absorption performance and sensing performance of the composite fabric (self-cleaning sensing composite coating) of the present invention are more excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a synthetic route diagram of the modified polyurea film prepared in Example 1 of the present invention.
[0051] Figure 2 The effect of different OHD contents on the static contact angle of PDMS-PUF.
[0052] Figure 3This is a transmission electron microscope image of the magnetic ferroferric oxide nanospheres prepared in Example 1 of the present invention.
[0053] Figure 4 This is a self-cleaning performance diagram of the self-cleaning sensor-type composite coating for fabric prepared in Example 1 of the present invention, NaCl is sodium chloride, NaOH is sodium hydroxide, HCl is hydrochloric acid, K2CrO4 is potassium chromate, Tea is tea, and Ink is ink.
[0054] Figure 5 This is a reflection loss diagram of the self-cleaning sensing composite coating for fabric prepared in Example 1 of the present invention.
[0055] Figure 6 This is a test chart of the underwater sensing performance of the self-cleaning sensing composite coating for fabric prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0056] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0057] Example 1
[0058] This embodiment provides a self-cleaning sensor type composite coating for fabrics, and the preparation method of the self-cleaning sensor type composite coating comprises the following steps:
[0059] (1) Cut the original cotton fabric into 4cm×4cm squares, activate it with NaOH solution for 0.5h and dry it. Mix 17mL of deionized water and 17mL of anhydrous ethanol (volume ratio 1:1) and add it to a beaker and stir evenly, then add 100μL of pyrrole and stir rapidly in an ice water bath to completely dissolve it. Dissolve 0.7g of FeCl3 in 5mL of deionized water, add it to the dissolved pyrrole dispersion and continue to stir magnetically evenly. Finally, add the activated original cotton fabric to the beaker, stir uniformly and react for 4h to obtain a polypyrrole composite fabric. At the same time, wash the reacted fabric with deionized water and dry it at 40°C to obtain a polypyrrole coating;
[0060] (2) immersing the successfully prepared polypyrrole fabric in a dispersion of magnetic Fe3O4 nanospheres and drying it in an oven at 40°C, repeating the above steps so that all the Fe3O4 nanospheres are deposited on the surface of the polypyrrole fabric to obtain a composite fabric of polypyrrole and ferroferric oxide, that is, a ferroferric oxide coating;
[0061] (3) Add NH2-PTMG-NH2 (polytetrahydrofuran ether glycol) (5 g), IPDI (isophorone diisocyanate) (4.44 g) and 10 mL THF (tetrahydrofuran) into a three-necked flask and stir mechanically. Slowly inject argon into the system to make the entire system in an inert gas state. Place the flask in a water bath and heat to 60°C. Keep the temperature for 8 hours, add octafluoro-1,6-hexanediol to the flask at a molar ratio of 0 to IPDI, add 10 mL THF and keep the temperature for 6 hours. After the reaction is completed, dry at 40°C to obtain a modified polyurea film (super hydrophobic polyurea film), that is, a hydrophobic polyurea modified coating;
[0062] (4) A modified polyurea film with better mechanical properties and hydrophobic properties was selected and mixed with 1H,1H,2H,2H-perfluorooctyltriethoxysilane (mass ratio of 1:1) and dissolved in 20 mL of a mixed solvent of tetrahydrofuran: anhydrous ethanol in a volume ratio of 1:1 to prepare a dispersion. The polypyrrole / ferroferric oxide fabric was immersed in it for 30 minutes and then dried in an oven at 40°C to obtain a self-cleaning sensing composite coating for the fabric.
[0063] The preparation method of magnetic ferroferric oxide nanoparticles is as follows:
[0064] 16mL ethylene glycol (EG), 0.26g FeCl3, 1.2g sodium acetate (NaAc), 0.4g poly (4-styrenesulfonic acid-maleic acid) sodium salt (PSSMA), 4.5mg acrylic acid (AA) and 20-50μL H2O were added to a beaker in sequence and magnetically stirred for 30min; then 0.24g NaOH was added to the beaker and stirred until the solution turned black and transparent; the solution was poured into a reactor, reacted at 190℃ for 9h and then cooled to room temperature; washed three times with 15mL anhydrous ethanol and 15mL deionized water respectively and centrifuged, and finally dispersed in 12.5mL deionized water to successfully prepare Fe3O4@PSSMA nanospheres (i.e., magnetic iron oxide nanospheres).
[0065] Figure 2 is the effect of different OHD contents on the static contact angle of PDMS-PUF (PDMS is polydimethylsiloxane, PDMS-PUF is the abbreviation of PDMS-modified polyurea film, and the subscripts represent different OHD contents; for example, PDMS-PUF1 represents PDMS-modified polyurea with a molar ratio of octafluoro-1,6-hexanediol to IPDI of 1); Figure 3 This is a transmission electron microscope image of the magnetic ferroferric oxide nanospheres prepared in Example 1 of the present invention; Figure 4This is a self-cleaning performance diagram of the self-cleaning sensor-type composite coating for fabrics prepared in Example 1 of the present invention, where NaCl is sodium chloride, NaOH is sodium hydroxide, HCl is hydrochloric acid, K2CrO4 is potassium chromate, Tea is tea, and Ink is ink; Figure 5 This is a reflection loss diagram of the self-cleaning sensing composite coating for fabrics prepared in Example 1 of the present invention; Figure 6 This is a test chart of the underwater sensing performance of the self-cleaning sensing composite coating for fabric prepared in Example 1 of the present invention.
[0066] from Figure 2 It can be seen that the prepared polyurea has good hydrophobicity, and with the increase of OHD (octafluoro-1,6-hexanediol) content, the contact angle of polyurea further increases, which can provide technical support for self-cleaning sensing composite coatings.
[0067] from Figure 3 It can be seen that Fe3O4 nanoparticles were successfully prepared, their shape was spherical, they were dispersed relatively evenly, and the average particle size was about 300nm.
[0068] from Figure 4 It can be seen that the prepared self-cleaning sensing composite coating has excellent hydrophobicity. Whether it is acid, alkali, salt or common stains in daily life, they can appear in the form of water droplets on its surface and will not directly contaminate the fabric.
[0069] from Figure 5 It can be seen that the prepared self-cleaning sensing composite coating has an electromagnetic wave absorption performance of about -14 dB, and has certain electromagnetic wave absorption performance.
[0070] from Figure 6 It can be seen that the prepared self-cleaning sensing composite coating can monitor signals in real time underwater, will not be affected by the underwater environment, and has stable output capabilities.
[0071] Example 2
[0072] This embodiment provides a self-cleaning sensor type composite coating for fabrics, and the preparation method of the self-cleaning sensor type composite coating comprises the following steps:
[0073] (1) Cut the original cotton fabric into 4cm×4cm squares, activate it with NaOH solution for 0.5h and dry it. Mix 17mL of deionized water and 17mL of anhydrous ethanol (volume ratio 1:1) and add it to a beaker and stir evenly, then add 100μL of pyrrole and stir rapidly in an ice water bath to completely dissolve it. Dissolve 0.7g of FeCl3 in 5mL of deionized water, add it to the dissolved pyrrole dispersion and continue to stir magnetically evenly. Finally, add the activated original cotton fabric to the beaker, stir uniformly and react for 4h to obtain a polypyrrole composite fabric. At the same time, wash the reacted fabric with deionized water and dry it at 40°C to obtain a polypyrrole coating;
[0074] (2) immersing the successfully prepared polypyrrole fabric in a dispersion of magnetic Fe3O4 nanospheres and drying it in an oven at 40°C, repeating the above steps so that all the Fe3O4 nanospheres are deposited on the surface of the polypyrrole fabric to obtain a composite fabric of polypyrrole and ferroferric oxide, that is, a ferroferric oxide coating;
[0075] (3) Add NH2-PTMG-NH2 (5 g), IPDI (4.44 g) and 10 mL THF into a three-necked flask and stir mechanically. Slowly inject argon into the system to make the entire system in an inert gas state. Place the flask in a water bath and heat it to 60°C. Keep the reaction warm for 8 hours, add octafluoro-1,6-hexanediol to the flask at a molar ratio of 0.5 to IPDI, add 10 mL THF and keep the reaction warm for 6 hours. After the reaction is completed, dry at 40°C to obtain a modified polyurea film (super hydrophobic polyurea film), that is, a hydrophobic polyurea modified coating;
[0076] (4) A modified polyurea film with better mechanical properties and hydrophobic properties was selected and mixed with 1H,1H,2H,2H-perfluorooctyltriethoxysilane (mass ratio of 1:1) and dissolved in 20 mL of a mixed solvent of tetrahydrofuran: anhydrous ethanol in a volume ratio of 3:1 to prepare a dispersion. The polypyrrole / ferroferric oxide fabric was immersed in it for 30 minutes and then dried in an oven at 40°C to obtain a self-cleaning sensing composite coating for the fabric.
[0077] The preparation method of magnetic ferroferric oxide nanoparticles is the same as that in Example 1.
[0078] Example 3
[0079] This embodiment provides a self-cleaning sensor type composite coating for fabrics, and the preparation method of the self-cleaning sensor type composite coating comprises the following steps:
[0080] (1) Cut the original cotton fabric into 4cm×4cm squares, activate it with NaOH solution for 0.5h and dry it. Mix 17mL of deionized water and 17mL of anhydrous ethanol (volume ratio 1:1) and add it to a beaker and stir evenly, then add 100μL of pyrrole and stir rapidly in an ice water bath to completely dissolve it. Dissolve 0.7g of FeCl3 in 5mL of deionized water, add it to the dissolved pyrrole dispersion and continue to stir magnetically evenly. Finally, add the activated original cotton fabric to the beaker, stir uniformly and react for 4h to obtain a polypyrrole composite fabric. At the same time, wash the reacted fabric with deionized water and dry it at 40°C to obtain a polypyrrole coating;
[0081] (2) immersing the successfully prepared polypyrrole fabric in a dispersion of magnetic Fe3O4 nanospheres and drying it in an oven at 40°C, repeating the above steps so that all the Fe3O4 nanospheres are deposited on the surface of the polypyrrole fabric to obtain a composite fabric of polypyrrole and ferroferric oxide, that is, a ferroferric oxide coating;
[0082] (3) Add a certain amount of NH2-PTMG-NH2 (5 g) and IPDI (4.44 g) and 10 mL of THF into a three-necked flask and stir mechanically. Slowly inject argon into the system to make the entire system in an inert gas state. Place the flask in a water bath and heat it to 60°C. Keep the reaction warm for 8 hours, add octafluoro-1,6-hexanediol to the flask at a molar ratio of 0.5 to IPDI, add 10 mL of THF and keep the reaction warm for 6 hours. After the reaction is completed, dry at 40°C to obtain a modified polyurea film (super hydrophobic polyurea film), that is, a hydrophobic polyurea modified coating;
[0083] (4) A modified polyurea film with better mechanical properties and hydrophobic properties was selected and mixed with 1H,1H,2H,2H-perfluorooctyltriethoxysilane (mass ratio of 2:1) and dissolved in 20 mL of a mixed solvent of tetrahydrofuran: anhydrous ethanol in a volume ratio of 3:1 to prepare a dispersion. The polypyrrole / ferroferric oxide fabric was immersed in it for 30 minutes and then dried in an oven at 40°C to obtain a self-cleaning sensing composite coating for the fabric.
[0084] The preparation method of magnetic ferroferric oxide nanoparticles is the same as that in Example 1.
[0085] Example 4
[0086] This embodiment provides a self-cleaning sensor type composite coating for fabrics, and the preparation method of the self-cleaning sensor type composite coating comprises the following steps:
[0087] (1) Cut the original cotton fabric into 4cm×4cm squares, activate it with NaOH solution for 0.5h and dry it. Mix 17mL of deionized water and 17mL of anhydrous ethanol (volume ratio 1:1) and add it to a beaker and stir evenly, then add 100μL of pyrrole and stir rapidly in an ice water bath to completely dissolve it. Dissolve 0.7g of FeCl3 in 5mL of deionized water, add it to the dissolved pyrrole dispersion and continue to stir magnetically evenly. Finally, add the activated original cotton fabric to the beaker, stir uniformly and react for 4h to obtain a polypyrrole composite fabric. At the same time, wash the reacted fabric with deionized water and dry it at 40°C to obtain a polypyrrole coating;
[0088] (2) immersing the successfully prepared polypyrrole fabric in a dispersion of magnetic Fe3O4 nanospheres and drying it in an oven at 40°C, repeating the above steps so that all the Fe3O4 nanospheres are deposited on the surface of the polypyrrole fabric to obtain a composite fabric of polypyrrole and ferroferric oxide, that is, a ferroferric oxide coating;
[0089] (3) Add NH2-PTMG-NH2 (5 g), IPDI (4.44 g) and 10 mL THF into a three-necked flask and stir mechanically. Slowly inject argon into the system to make the entire system in an inert gas state. Place the flask in a water bath and heat it to 60°C. Keep the reaction warm for 8 hours, add octafluoro-1,6-hexanediol to the flask at a molar ratio of 1 to IPDI, add 10 mL THF and keep the reaction warm for 6 hours. After the reaction is completed, dry at 40°C to obtain a modified polyurea film (super hydrophobic polyurea film), that is, a hydrophobic polyurea modified coating;
[0090] (4) A modified polyurea film with better mechanical properties and hydrophobic properties was selected and mixed with 1H,1H,2H,2H-perfluorooctyltriethoxysilane (mass ratio of 2:1) and dissolved in 20 mL of a mixed solvent of tetrahydrofuran: anhydrous ethanol in a volume ratio of 3:1 to prepare a dispersion. The polypyrrole / ferroferric oxide fabric was immersed in it for 30 minutes and then dried in an oven at 40°C to obtain a self-cleaning sensing composite coating for the fabric.
[0091] The preparation method of magnetic ferroferric oxide nanoparticles is the same as that in Example 1.
[0092] Example 5
[0093] This embodiment provides a self-cleaning sensor type composite coating for fabrics, and the preparation method of the self-cleaning sensor type composite coating comprises the following steps:
[0094] (1) Cut the original cotton fabric into 4cm×4cm squares, activate it with NaOH solution for 0.5h and dry it. Mix 17mL of deionized water and 17mL of anhydrous ethanol (volume ratio 1:1) and add it to a beaker and stir evenly, then add 100μL of pyrrole and stir rapidly in an ice water bath to completely dissolve it. Dissolve 0.7g of FeCl3 in 5mL of deionized water, add it to the dissolved pyrrole dispersion and continue to stir magnetically evenly. Finally, add the activated original cotton fabric to the beaker, stir uniformly and react for 4h to obtain a polypyrrole composite fabric. At the same time, wash the reacted fabric with deionized water and dry it at 40°C to obtain a polypyrrole coating;
[0095] (2) immersing the successfully prepared polypyrrole fabric in a dispersion of magnetic Fe3O4 nanospheres and drying it in an oven at 40°C, repeating the above steps so that all the Fe3O4 nanospheres are deposited on the surface of the polypyrrole fabric to obtain a composite fabric of polypyrrole and ferroferric oxide, that is, a ferroferric oxide coating;
[0096] (3) Add a certain amount of NH2-PTMG-NH2 (5 g) and IPDI (4.44 g) and 10 mL of THF into a three-necked flask and stir mechanically. Slowly inject argon into the system to make the entire system in an inert gas state. Place the flask in a water bath and heat it to 60°C. Keep the reaction warm for 8 hours, add octafluoro-1,6-hexanediol to the flask at a molar ratio of 1 to IPDI, add 10 mL of THF and keep the reaction warm for 6 hours. After the reaction is completed, dry at 40°C to obtain a modified polyurea film (super hydrophobic polyurea film), that is, a hydrophobic polyurea modified coating;
[0097] (4) A modified polyurea film with better mechanical properties and hydrophobic properties was selected and mixed with 1H,1H,2H,2H-perfluorooctyltriethoxysilane (mass ratio of 3:1) and dissolved in 20 mL of a mixed solvent of tetrahydrofuran: anhydrous ethanol in a volume ratio of 3:1 to prepare a dispersion. The polypyrrole / ferroferric oxide fabric was immersed in it for 30 minutes and then dried in an oven at 40°C to obtain a self-cleaning sensing composite coating for the fabric.
[0098] The preparation method of magnetic ferroferric oxide nanoparticles is the same as that in Example 1.
[0099] Effect verification
[0100] Experimental object: Examples 1 to 5 prepared a self-cleaning sensor-type composite coating (fabric) for fabric.
[0101] Experimental methods:
[0102] Water contact angle test: After cutting the fabric, stick double-sided tape on a glass slide, lay the fabric flat on the glass slide, and place it under a video optical contact angle tester to test the static water contact angle (WCA) of the fabric. Test each strip of fabric three times in parallel at different positions, take pictures and record the average value.
[0103] Wave absorption measurement method: The MCPP fabric was cut into long strips and then fully mixed with paraffin (mass ratio of 40%) and pressed into a ring with a mold, and the electromagnetic parameters of the MCPP fabric at 2-18GHz were tested using an E5080A vector network analyzer; the complex dielectric constant (εr=ε′-jε″) and complex magnetic permeability (μr=μ′-jμ″) of the MCPP fabric were measured in particular; the real part (ε′) and imaginary part (ε′) of the complex dielectric constant represent the electrical energy storage and electrical energy loss capabilities of the dielectric, respectively, while the real part (μ′) and imaginary part (μ″) of the complex magnetic permeability are usually used to represent the magnetic energy storage and magnetic energy loss capabilities of magnetic materials; in order to intuitively observe the effect of the number of immersion times of the MCPP fabric on the wave absorption performance, we also tested the reflection loss value (RL) and effective absorption bandwidth (EAB) of the MCPP fabric, and the results are shown in Table 1 below.
[0104] Table 1 Measurement results of water contact angle and wave absorption
[0105] Example Example 1 Example 2 Example 3 Example 4 Example 5 Water contact angle 105.4° 113.5° 144.5° 148.4° 154.5° Wave Absorption -14dB -14dB -14dB -14dB -14dB
[0106] As can be seen from Table 1, the fabric prepared by the embodiment of the present invention has good hydrophobicity. As the content of OHD (octafluoro-1,6-hexanediol) increases, the contact angle of the fabric further increases, which can provide technical support for self-cleaning sensing composite coatings. By optimizing the amount of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane added, it can be seen that the increase in the content of 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane will reduce the surface energy and further improve the hydrophobicity. Moreover, when the mass ratio of the modified polyurea film to 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane is 3: 1, the hydrophobicity is optimal. Moreover, the fabric prepared by the present invention has an electromagnetic wave absorption performance of about -14dB, and has certain electromagnetic wave absorption performance.
[0107] It should be understood that the disclosed invention is not limited only to the specific method, scheme and material of description, because these all can change.It should also be understood that the terminology used herein is only for the purpose of describing specific embodiment scheme, rather than being intended to limit the scope of the present invention, and the scope of the present invention is only limited to the appended claims.
[0108] Those skilled in the art will also recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments of the invention described herein. Such equivalents are also intended to be encompassed by the appended claims.
Claims
1. A self-cleaning sensor-type composite coating for fabrics, characterized in that: The self-cleaning sensing composite coating comprises a polypyrrole coating, a ferrosoferric oxide coating and a hydrophobic polyurea modified coating.
2. The method for preparing the self-cleaning sensor-type composite coating for fabrics according to claim 1, characterized in that: The preparation method comprises the following steps: Step S1, after activating the fabric in a sodium hydroxide solution, a polypyrrole composite fabric is obtained by in-situ growth of polypyrrole, and the polypyrrole coating is obtained by washing and drying. Step S2, placing the dried polypyrrole composite fabric in a dispersion of magnetic ferroferric oxide nanospheres, immersing the fabric in the dispersion, and then drying the fabric to obtain a polypyrrole and ferroferric oxide composite fabric, that is, a ferroferric oxide coating; Step S3, adding polydimethylsiloxane and diisocyanate into an organic solvent to react to obtain a polyurea prepolymer, and then adding a fluorine-containing organic substance to obtain a super-hydrophobic polyurea film, that is, a hydrophobic polyurea modified coating; Step S4, dissolving the super-hydrophobic polyurea film and the organosiloxane in a mixed solvent and stirring evenly to obtain a mixed dispersion; placing the polypyrrole and ferroferric oxide composite fabric in the mixed dispersion, immersing it in the mixed dispersion, and then drying it to obtain the self-cleaning sensor-type composite coating for the fabric.
3. The preparation method according to claim 2, characterized in that: The organic solvent in step S3 is selected from one or more of acetone, butanone, ether, toluene, xylene, tetrahydrofuran, ethylene glycol, N,N-dimethylformamide and N,N-dimethylacetamide; The fluorine-containing organic compound in step S3 is octafluoro-1,6-hexanediol.
4. The preparation method according to claim 2, characterized in that: The molar ratio of diisocyanate to fluorine-containing organic matter in step S3 is 1:0-1.
5. The preparation method according to claim 2, characterized in that: The mixed solvent in step S4 is tetrahydrofuran and anhydrous ethanol, and the volume ratio of the tetrahydrofuran to the anhydrous ethanol is 1 to 3:
1.
6. The preparation method according to claim 2, characterized in that: The mass ratio of the super hydrophobic polyurea film to the organosiloxane in step S4 is 0.5 to 2:
1.
7. The preparation method according to claim 2, characterized in that: The fabric is one of polyester fabric, cotton fabric, silk fabric and wet-spun fabric.
8. A self-cleaning sensor-type composite coating, characterized in that: The self-cleaning sensing composite coating comprises a polypyrrole coating, a ferrosoferric oxide coating and a hydrophobic polyurea modified coating.
9. Use of the self-cleaning sensor-type composite coating for fabrics according to claim 1 in preparing self-cleaning sensor-type fabrics.
10. Use of the self-cleaning sensor type composite coating according to claim 8 in preparing self-cleaning sensor type fabric.
Citation Information
Patent Citations
Preparation method for silicofluoride-contained polyurethane water repellent finishing agent
CN102702465A
Preparing method and application of anti-freezing type bi-component polyurea waterproof paint for bridges
CN106010175A
Composite coating, composite coating and preparation method of composite coating
CN118725661A
Preparation method of super-hydrophobic fabric for anti-icing, optical / electric heating and electromagnetic induction heat deicing
CN118854677A
Production of self-cleaning surfaces on textile coatings
US20060128239A1
Cited By
Preparation method and application of multi-layer light skin
CN121515583A
Method for manufacturing a multilayer lightweight skin and use thereof
CN121515583B